KARAKTERISTIK PEDESTRIAN DI JALAN TANJUNG DUREN RAYA, KOTA JAKARTA BARAT - Tanjung, Deva Perdana (Jurnal Planesa (Planologi), 2025)
This research discusses the characteristics of pedestrian paths on Jalan Tanjung Duren Raya in West Jakarta City. The results of observations and analysis indicate that the width of the pedestrian paths meets the standards and connects various land uses such as offices, commercial areas, education, and others. The surface of the pedestrian paths is relatively even, stable, not slippery, and its elevation meets the required standards. However, there are obstacles that hinder the accessibility and comfort of pedestrians, such as inappropriate use of the paths, intrusion by motorized vehicles, and lack of cleanliness. Suggestions for improving the pedestrian paths include managing disruptive parking, enhancing facilities for people with disabilities, adding necessary amenities, and increasing surveillance to maintain order on the pedestrian paths